Health utilities of patients with multiple sclerosis and neuromyelitis optica spectrum disorders in Thailand - Sasitorn Siritho (2018)
© 2018 Background: Multiple sclerosis (MS) and neuromyelitis optica spectrum (NMOSD) cause several symptoms that negatively impact on patient's quality of life. No study has ever conducted to examine the quality of life of MS and NMOSD patients, especially in terms of health utility, among the non-western population. This study aims to examine health utility among MS and NMOSD patients in Thailand. Methods: A multicenter cross-sectional study including 104 MS and 186 NMOSD patients was conducted. Health utility was measured using EQ-5D questionnaire. Demographic data, clinical data and Expanded Disability Status Scales (EDSS) were also collected. Results: Health utility scores of MS or NMOSD were 0.41 ± 0.36 and 0.41 ± 0.32, respectively. No significant difference between MS and NMOSD in term of health utility score was found. Pain, mobility, and anxiety/depression are the three most affected domains among both MS and NMOSD patients. Age at onset less than 40 years and EDSS score less than or equal to 2.5 were significantly associated with higher health utility score in MS and NMOSD patients. Conclusion: Our findings clearly demonstrated the negative impact of MS and NMOSD on patients’ health-related quality of life. Effective interventions that target pain, mobility, and anxiety/depression should be provided to improve quality of life of these patients. Health utility estimates from this study can be used as an important input for economic evaluations of treatments for MS and NMOSD to inform resource-allocation decisions.